1994
DOI: 10.1111/j.1365-246x.1994.tb03968.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper-mantle velocity structure beneath the Siberian platform

Abstract: S U M M A R YWe present a new velocity model for the continental upper mantle beneath central Siberia based on observations of the 1982 'RIFT' Deep Seismic Sounding (DSS) profile. Three Peaceful Nuclear Explosions (PNE) were detonated to provide energy for the 2600 km long profile that extends from the Yamal Peninsula to the Mongolian border SE of Lake Baikal. In this paper, we model seismic recordings from the northernmost explosion since data from that shot shows unambiguous arrivals from the mantle-transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The conditional homogeneity of the layer is due to the paucity of data on its properties. Figure 3 shows the traveltime curves of the first arrivals and subsequent phases of reflected waves along the Meteorite profile, supplemented after (Egorkin, 1999;Pavlenkova et al, 1996;Priestley et al, 1994). The greatest attention is attracted by the apparent velocities of first-arrival waves increased dramatically to 8.7-8.9 km/s at different offset distances (shaded in Fig.…”
Section: Seismic Structure Of the Upper Mantlementioning
confidence: 94%
“…The conditional homogeneity of the layer is due to the paucity of data on its properties. Figure 3 shows the traveltime curves of the first arrivals and subsequent phases of reflected waves along the Meteorite profile, supplemented after (Egorkin, 1999;Pavlenkova et al, 1996;Priestley et al, 1994). The greatest attention is attracted by the apparent velocities of first-arrival waves increased dramatically to 8.7-8.9 km/s at different offset distances (shaded in Fig.…”
Section: Seismic Structure Of the Upper Mantlementioning
confidence: 94%
“…700 km) show that the upper mantle of the Siberian Craton is strongly heterogeneous, with the presence of a series of thin high-velocity and low-velocity layers beneath some parts of Siberia (Fuchs and Wenzel, 1997). Velocity anomalies associated with these multiple LVZs may sometimes be interpreted as the LAB (Priestley et al, 1994), although many profiles do not show any velocity change at ca. 200-250 km depth Suvorov et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Because the wavelength of body phases typically used to study the discontinuities is of the order of the length scale of the discontinuity itself, any conclusive seismic estimation of the fine structure of the 410 is made difficult by the apparent transition impedance and thickness potentially being as much a function of source spectral content as actual structure [Burdick and Helmberger, 1978; Hell-/rich and . Reported thicknesses vary by up to a factor of 10, from 35 km Under the central Eurasian craton [Priestley et al, 1994] to 2-4 km under oceanic tiple ScS bounces, whereas more recent studies have found slightly positive to no correlation, as inferred from P to SV conversions and long-period SS precursors [Shearer, 1993;Flanagan and Shearer, 1998]. From laboratory experiments and thermodynamic calculations, it is expected on the basis of Clapeyron slope magnitudes that the 410-km discontinuity should have more topography than the 670-km discontinuity ], but seismically the opposite has been found [Shearer, 1991;Flanagan and Shearer, 1998].…”
Section: Introductionmentioning
confidence: 99%